Understanding capacity fading of the LiVO3 cathode material by limiting the cutoff voltage. Issue 13 (14th March 2019) - Fu, Xifan; Pu, Xiangjun; Wang, Huiming; Zhao, Dong; Liu, Guangrong; Zhao, Dong; Chen, Zhongxue
Abstract : The LiVO3 cathode cycled in a narrower voltage window demonstrates better structural stability and outstanding cycling performance over 400 cycles. Abstract : The effects of discharge cutoff voltages on the structural evolution and electrochemical performance of the LiVO3 cathode upon cycling are investigated by electrochemical measurements, electrochemical impedance spectroscopy, ex situ X-ray diffraction, Raman spectra, Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. It is found that a lower cutoff voltage causes formation and accumulation of unstable V 4+ ions on the surface of the electrode, which easily leads to severe structural deterioration and capacity fading. A limited cutoff voltage between 3.5 and 1.5 V can effectively enhance the structural stability and consequently the electrode demonstrates 75.9% capacity retention and neglectable working voltage decay over 400 cycles. The result that the operation voltage range strongly affects the structural stability of cycled LiVO3 provides a new insight into exploring feasible approaches to achieve highly stable LiVO3 and other vanadium-based electrodes for lithium-ion batteries.